Effects of collagen cross-linking on corneal topographic characteristics in the patients with keratoconus (Journal of National Institute of Ophthalmology, 2025)
Background: Keratoconus is a bilateral, non-inflammatory, progressive disorder characterized by corneal thinning and protrusion, progressive myopia, and irregular astigmatism. Available treatment for keratoconus is the use of spectacles, soft contact lenses, rigid or gas permeable contact lens, collagen cross-linking, intracorneal ring segment implantation using laser or mechanical channel creation, keratoplasty either penetrating or deep anterior lamellar for severe disease. Collagen cross linking is the treatment of choice for primary Keratoconus of progressive variety. It halts progression of Keratoconus and later improves patient's vision. Objectives: To  evaluate effect of Corneal Collagen Cross Linking (CxL) on Corneal Topographic characteristics (K , K , Kapex,  corneal thickness). Methodology: This prospective observational study was conducted in the department of  Cornea, National Institute of Ophthalmology and Hospital, Dhaka from January 2019 to April 2020 on 60 eyes of  60 patients of keratoconus. Patients were selected purposively based on specific selection criteria. Corneal  Collagen cross-linking(CxL) were done in all the selected patients by a single competent cornea specialist.  They  were followed up on 1 month, 3 months and 6 months after procedure.  K , K  and Kapex and corneal thickness  12 were assessed in each follow-up. All the relevant data were recorded in a pre-designed data collection sheet. Data  were analyzed by using window software SPSS ver. 21. Ethical approval was taken from ethical review  committee of National Institute of Ophthalmology and Hospital, Dhaka prior to commencement of the study.  Results:  The study comprised participants aged predominantly between 20 to 30 years (45%), with more males  (66.7%) than females (33.3%). Post collagen cross-linking (CxL) treatment, significant reductions were observed  in flat keratometry (K ), steep keratometry (K ), steepest keratometry (Kapex), and central corneal thickness  12 1(CCT) across all assessment periods (1, 3, and 6 months). Notably, K decreased from 45.66±3.43 diopters at 2baseline to 43.29±3.29 diopters at 6 months, K decreased from 50.22±5.93 diopters to 47.12±4.48 diopters, Kapex decreased from 54.50±7.38 diopters to 51.32±5.13 diopters, and CCT decreased from 467.53±37.38 micrometers to 425.03±26.41 micrometers (p